Cover Feature: Stereoselective Oxidative Mannich Reaction of Ketones with Dihydrodibenzo‐Oxazepines via a Merger of Photoredox‐/Electro‐Catalysis with Organocatalysis (ChemSusChem 12/2022). Issue 12 (30th May 2022) - Hussain, Yaseen; Sharma, Deepak; Kotwal, Namrata; Kumar, Indresh; Chauhan, Pankaj
Abstract : The Cover Feature shows (left side) that the merger of visible light photoredox catalysis or electrocatalysis with chiral organocatalysis provides direct access to diastereo‐ and enantio‐enriched 11‐substituted 10, 11‐dihydrodibenzo[ b, f ][1, 4]oxazepanes. Both combinations afforded greener and sustainable alternatives to avoid the direct use of toxic and lacrimatory tear gas components (i.e., CR gas, right side). More information can be found in the Research Article by Y. Hussain, D. Sharma, et al .